STRATEGI BISNIS PT PEMBANGKITAN JAWA-BALI DALAM MENGHADAPI CRASH PROGRAM 10.00 MW - , Jayadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Energy Diversification Acceleration Program (PPDE) or known by 10,000 MW Crash Program is one government program to address the shortage of electrical energy supply in the country. This program will involve power generation companies both government and independent power producer. PT Pembangkitan Jawa-Bali as one of the government-owned power companies are trying to take a significant role in the program. This study aims to determine whether the business strategy of PT Pembangkitan Jawa-Bali is still relevant to current conditions and future, and formulate a suitable type of value discipline to be applied to deal with 10,000 MW Crash Program. From the discussion that has been done, it can be concluded that the PT Pembangkitan Jawa-Bali have been on track with the company roadmap to become a world-class power generation companies. PT Pembangkitan Jawa-Bali suitable implement operational excellence strategy in running its business processes to cope with the 10,000 MW crash program. Operational excellence is expected to be a reference value of PT Pembangkitan Jawa-Bali in formulating strategies to generate electric power at more competitive prices as expected by the consument.